2016
DOI: 10.1001/jamafacial.2016.0673
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Change in Lower Eyelid Position in Patients Undergoing Transcutaneous Skin-Muscle Flap Lower Eyelid Blepharoplasty

Abstract: IMPORTANCETranscutaneous lower eyelid blepharoplasty is a commonly performed procedure with a postoperative risk of eyelid malposition.OBJECTIVE To quantify the change in lower eyelid position after transcutaneous lower eyelid blepharoplasty. DESIGN, SETTING, AND PARTICIPANTSThis retrospective medical record review describes patients who underwent transcutaneous blepharoplasty at a private facial plastic surgery practice. Patients with less than 3 months of follow-up, a history of periocular trauma, and concur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Taban et al [ 13 ] reported that the change in lower eyelid position was not statistically significant after a transconjunctival lower blepharoplasty with or without a skin pinch. Sultan et al [ 14 ] reported that transcutaneous skin-muscle flap lower eyelid surgery increased the distance between the pupil and lower eyelid margin. Segal et al [ 15 ] reported that transconjunctival blepharoplasty with or without skin resurfacing did not induce lid retraction but elevated the lower lid in the majority of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Taban et al [ 13 ] reported that the change in lower eyelid position was not statistically significant after a transconjunctival lower blepharoplasty with or without a skin pinch. Sultan et al [ 14 ] reported that transcutaneous skin-muscle flap lower eyelid surgery increased the distance between the pupil and lower eyelid margin. Segal et al [ 15 ] reported that transconjunctival blepharoplasty with or without skin resurfacing did not induce lid retraction but elevated the lower lid in the majority of patients.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] In a retrospective review of 100 patients, Sultan et al found that transcutaneous skin-muscle lower eyelid blepharoplasty produced a small, predictable eyelid position change of 0.33 mm from the pupil to the lower eyelid margin and 0.32 mm from the lateral limbus to the lower eyelid margin. 13 While they reported a low rate of revision procedures, we have anecdotally found that many patients are dissatisfied with even this small amount of eyelid change.…”
mentioning
confidence: 87%
“…The distraction test evaluates whether the lower lid can be pulled > 6 mm from the globe. 11 If this is the case, lid support is poor. Poor lid support can lead to several issues postoperatively if not addressed intraoperatively including ectropion, dry eye, exposure keratitis, epiphora, etc.…”
Section: Pearls Of Lower Eyelid Examinationmentioning
confidence: 99%